Transition, Taxation and the State. - Turley, Gerard (Transition and development., 2007)
In economic terms three of the most important and controversial issues of our times are transition, taxation and the role of the state. This book examines the core associated problems of tax payment and collection in the context of transition from a centrally planned economy to a market economy.